Constitutional indocyanine green excretion defect in a Chinese patient without underlying liver disease: case report and mechanistic insights - Ma, Xueying; Tian, Fei; Zhou, Shuanghao; Li, Jianjun; Liu, Yankun; Hui, Ying; Ma, Xiangming (Frontiers in Medicine, 2026)
Constitutional indocyanine green excretion defect (CIED) is a rare disorder characterized by markedly delayed plasma indocyanine green disappearance (ICG-R15 > 50%) despite normal results from conventional liver function tests. We present case a case involving 60-year-old woman diagnosed with CIED, which represents the first documented case in a Chinese patient without any underlying liver disease. This case expands the recognized geographic and epidemiologic spectrum of CIED. Whole-exome sequencing revealed no deletions or pathogenic variants in genes encoding established ICG transporters [SLCO1B1 (OATP1B1), SLCO1B3 (OATP1B3), SLC10A1 (NTCP), and ABCC2 (MRP2)], excluding conventional mechanistic explanations. Our integrated clinical and molecular characterization offers novel insights into this rare disorder. These findings suggest a novel pathogenesis independent of known transporter deficiencies, highlighting the need for further research and underscoring the importance of integrating multidimensional clinical data for accurate interpretation of ICG test results.